Philippine flora the online compendium of native vines in the Philippines for landscape architecture - San Antonio-Perion, Sharon (College of Architecture, University of the Philippines Diliman, 2014)
The Philippines is blessed with floral biodiversity which brings great potential and advantage to the country's landscape architecture because of extraordinary wealth in planting materials. However, there are limited reference materials about native plants in the Philippines. And it has been a continuous conquest to study native plants in the country. For instance, in the plant group of trees alone, taxonomists and plant experts decade of years is not enough to study the vast number of species. This in effect leads to neglect of other plant group particularly vines. "The vine flora is considered as one of the dark areas in taxonomy due to limited studies and researches conducted on the plant group" (Maningas 2007). Therefore, how can the existing limited body of knowledge on Philippine native vines be enriched and made available for wider landscape architecture use? The study intended to asses the knowledge and level of awareness about Philippines native vines; to provide a list suitable for landscape architecture that are distinguished based on properties, attributes and characteristics, among other aspects; to create a user-friendly website and evaluate it through user-interface. The study selected 25 Philippine native vines for landscape architecture based on three major criteria such as their availability, adaptability and aesthetics. It is observed that availability is a major consideration in selection of Philippines native vines in landscape design. Because even if native vines have high aesthetic value, still their use and recommendation especially from landscape architects and related professionals is highly dependent on their availability and adaptability. Unfortunately, the study showed that majority of the respondents are not aware of the indigenous and endemic vines species in the country. The Online Compendium of Philippine native vines for landscape architecture use the effective platform of the internet to widely provide an easy access source of information for landscape architects, students and general public.